Wide-band measurement and ray-tracing simulation of the 1900-MHz indoor propagation channel comparison criteria and results. - Degli-Eposti, V. (IEEE Transactions on antennas and propagation)
The results of a wide-hand indoor measurement campaign are compared with the corresponding simulation results provided by a 3-D ray-tracing field prediction model. A novel comparison criterion based on the ?scale level? concept is presented and used in the present work. On the basis of the cited criterion, the validity domain of the ray-tracing tool, the degree of accuracy of the prediction as a function of the scale level, and future necessary improvement of the model have been identified and discussed. The comparisons refer to a variety of propagation parameters such as path loss, delay spread, coherence bandwidth, etc. The influence of environment description (with or without furniture) is also analyzed. The paper shows that the 3-D ray tracing model can be a useful tool for the analysis of indoor propagation and for the design and the implementation of indoor wide-band applications